Sosialisasi Pentingnya Komunikasi Keluarga Dalam Pengawasan Anak Berinternet Di Era Digital - Saputraa, Azis Dwi; Prasetyo, Anung; Fariz, Muhammad Hasnan; Putri, Elissa Erna; Haurissa, Laurence Ester Margaretha; Harahap, Hamida Syari (Jurnal Loyalitas Sosial: Journal of Community Service in Humanities and Social Sciences, 2025)
The internet is an essential part of daily life, including for children, but lack of parental supervision can lead to negative effects such as internet addiction. This article explores the role of family communication in monitoring children's internet use in the digital era, with a case study in RW 07 Harapan Mulya Village. A socialization program was conducted to raise parents' awareness of the importance of supervision. The method involved three stages: (1) Preparation, including creating materials and media to attract public attention; (2) Implementation, which involved educating the community through socialization; and (3) Evaluation and follow-up, where students collected feedback on the program’s effectiveness. The results showed that participants were enthusiastic and recognized the importance of family communication in minimizing the internet's negative impact. Surveys and interviews revealed that 30.4% of children initially spent three hours online daily, but after parental education, this decreased to 1–2 hours. Parents are encouraged to actively guide their children, set clear boundaries, and foster open communication to help them use technology wisely.